Amelogenesis Imperfecta - An account of Three Generations affected in a Family - G Sarat; Arindam Sarkar; S Suhas; Keerthilatha M Pail (Wolters Kluwer Medknow Publications, 2004)
Amelogenesis Imperfecta is a hereditary condition affecting dental enamel without any systemic manifestation. This condition can be inherited as either Autosomal or X-linked. In this case report, we discuss with the help of Pedigree Analysis, an account of three generations in a family affected by Autosomal Dominant, Hypoplastic type of Amelogenesis Imperfecta.